2010
DOI: 10.1016/j.nima.2010.02.114
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of fissionable material behaviour in fission chambers

Abstract: Keywords:Fission chamber BR2 DEMO IFMIF Uncertainty cross-sections A comprehensive study is performed in order to assess the pertinence of fission chambers coated with different fissile materials for high neutrón flux detection. Three neutrón scenarios are proposed to study the fast component of a high neutrón flux: (i) high neutrón flux with a significant thermal contribution such as BR2, (ii) DEMO magnetic fusión reactor, and (iii) IFMIF high flux test module.In this study, the inventory code ACAB is used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…It is important to notice the influence of the cross section uncertainties in the predicted value. Calculations performed for a 238 U deposit showed that, in BR2 conditions, it could lead to 14% relative error in sensitivity to fast neutrons [5].…”
Section: Evolution Of the Neutron Sensitivity Of The Cfur43mentioning
confidence: 99%
“…It is important to notice the influence of the cross section uncertainties in the predicted value. Calculations performed for a 238 U deposit showed that, in BR2 conditions, it could lead to 14% relative error in sensitivity to fast neutrons [5].…”
Section: Evolution Of the Neutron Sensitivity Of The Cfur43mentioning
confidence: 99%
“…Three boundary conditions complete (2): (a) the electronic density is zero at the cathode surface, (b) the ionic density is zero at the anode surface, (c) a voltage difference, , being applied between anode and cathode for charge collection, we have (3) where is any possible path linking the anode to the cathode. Using a perturbation method, we had obtained analytical solutions for (2) with boundary conditions (a) to (c).…”
Section: A Key Equationsmentioning
confidence: 99%
“…Because of their reduced volume and their robustness, SMF chambers have become standard power monitors in many commercial and research nuclear reactors. Their use is extending to other neutron sources, such as spallation targets, and is under investigation for the monitoring of fusion devices [1]- [3].…”
Section: Introductionmentioning
confidence: 99%
“…Fission chambers are widely used in online neutron flux measurement. It could be adopt for not only the fission neutron field but also the fusion neutron field [3].…”
Section: Introductionmentioning
confidence: 99%